2023
DOI: 10.1177/02601060231186439
|View full text |Cite
|
Sign up to set email alerts
|

The effect of curcumin supplementation on functional strength outcomes and markers of exercise-induced muscle damage: A systematic review and meta-analysis

Robert A Oxley,
Daniel J. Peart

Abstract: Background: Curcumin is a polyphenol derived from the Curcuma longa L (turmeric) plant and has gained attention through its perceived anti-inflammatory characteristics. The potential interaction with exercise-induced muscle damage (EIMD) and delayed onset muscle soreness (DOMS) has led to investigation of curcumin as a post-exercise strategy that may have the potential to lessen acute reductions in functional strength (FS) following physical activity. Aim: The purpose of this review is to assess the evidence e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Curcumin can promote healthy cardiovascular function by improving endothelial function and balancing blood pressure. Previous studies on the post-exercise recovery effects of curcumin indicated that it can alleviate muscle damage, such as pain and inflammation, after exercise [ 59 ]. The application of curcumin in sports nutrition has been attracting increasing attention recently.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin can promote healthy cardiovascular function by improving endothelial function and balancing blood pressure. Previous studies on the post-exercise recovery effects of curcumin indicated that it can alleviate muscle damage, such as pain and inflammation, after exercise [ 59 ]. The application of curcumin in sports nutrition has been attracting increasing attention recently.…”
Section: Discussionmentioning
confidence: 99%